Pelanggaran Etika Jurnalistik dalam Pemberitaan Pemilu 2024 di Metro TV - Muarif, Nur Affan; Ihsan, Fikri Nur; Fawwaz, Muhammad Hafizh; Junaedi, Fajar (Jurnal JTIK (Jurnal Teknologi Informasi dan Komunikasi), 2024)
This article discusses the importance of Journalistic Ethics in the 2024 Election News on Metro TV. Television as a political communication medium is very effective in delivering information to the public. Political parties utilize television to convey their vision, address community issues, and build public support. Journal Ethics, as a set of ethical guidelines for journalists, is essential to ensure integrity and professionalism in reporting. This article highlights the importance of journalistic ethics based on Law No.40 of 1999 on the Indonesian Journalist Code of Ethics (KEWI), which aims to improve media integrity. The research used a qualitative method with descriptive analysis to identify ethical issues in the coverage of the 2024 General Election on Metro TV. Findings included a lack of transparency, non-neutral language, lack of information verification, sensational reporting, and the need for Metro TV’s commitment to ethical journalism to improve the quality of reporting.